دور التسويق الإلكتروني في تعزيز العلامة التجارية للمؤسسة دراسة حالة مؤسسة "موبيليس سوق أهراس - حسان خيري; عبد النور بوشوك (My University, 2022)
This study aims to shed light on the role of e-marketing in enhancing the organization’s brand, by highlighting the importance of the optimal e-marketing mix for institutions and various e-marketing strategies, in the midst of the tremendous technological developments and changing communication habits between individuals who are spending more time through social media, Virtual societies and other means of instantaneous communication that affected the shape of the relationship between institutions and customers. We also look through this study to ways to enhance the brand of institutions in the context of keeping pace with the requirements of modern e-marketing, by adopting a broad modern concept that includes the value of the brand in its four dimensions (perceived quality, mental image, brand reputation, and customer loyalty), which ensures the efficiency of institutions. greater awareness of their products. In order to know the role of e-marketing in promoting the brand, Mobilis customers were targeted, through a questionnaire that was randomly distributed to 150 actual dealers of the brand, after which the data was unloaded and analyzed according to the SPSS program, which enabled us to reach the most important result of this study; It is that e-marketing affects the various dimensions of the components of the brand value of the Mobilis Corporation in the state of Souk Ahras, and the study reached a set of recommendations, the most important of which is the need for the Mobilis Corporation to pay attention to diversifying its e-marketing strategies because of its impact on the various dimensions of the value of the brand and its position in the online market especially ................................................ تهدف هذه الدراسة إلى تسليط الضوء على دور التسويق الإلكتروني في تعزيز العلامة التجارية للمؤسسة، من خلال إبراز أهمية المزيج التسويقي الإلكتروني الأمثل للمؤسسات ومختلف الاستراتيجيات التسويقية الالكترونية، في خضم التطورات التكنلوجية الهائلة وتغير عادات الاتصال بين الأفراد الذين أصبحوا يمضون وقتا أكبر عبر وسائط التواصل الاجتماعي والمجتمعات الافتراضية وغيرها من وسائل الاتصال اللحظي التي أثرت على شكل العلاقة بين المؤسسات والزبائن. كما نتظرق من خلال هذه الدراسة إلى سبل تعزيز العلامة التجارية للمؤسسات في إطار مواكبتها لمتطلبات التسويق الإلكتروني الحديث، من خلال تبنيها لمفهوم حديث واسع يتضمن قيمة العلامة التجارية بأبعادها الأربعة )الجودة المدركة، الصورة الذهنية، شهرة العلامة، ولاء الزبائن(، التي تضمن للمؤسسات نجاعة أكبر للتعريف بمنتجاتها. ومن أجل معرفة دور التسويق الالكتروني في تعزيز العلامة التجا رية، تم استهداف زبائن مؤسسة موبيليس، من خلال الاستبيان الذي تم توزيعه بطريقة عشوائية على 150 متعامل فعلي للعلامة، ليتم بعد ذلك الذي مكننا من التوصل إلى أهم نتيجة لهذه الدراسة؛ وهي أن SPSS تفريغ البيانات وتحليلها وفقا لبرنامج التسويق الالكتروني يؤثر على مختلف أبعاد العناصر المكونة لقيمة العلامة التجارية لمؤسسة موبيليس بولاية سوق أهراس، كما توصلت الدراسة إلى مجموعة من التوصيات، أهمها ضرورة اهتمام مؤسسة موبيليس بتنويع استراتيجياتها التسويقية الإلكترونية لما لها من أثر على مختلف أبعاد قيمة العلامة التجا رية، ومكانتها بالسوق الإلكتروني خاصة.